2007
DOI: 10.1128/jb.00738-07
|View full text |Cite
|
Sign up to set email alerts
|

Transducing Particles of Staphylococcus aureus Pathogenicity Island SaPI1 Are Comprised of Helper Phage-Encoded Proteins

Abstract: The relationship between the composition of SaPI1 transducing particles and those of helper phage 80␣ was investigated by direct comparison of virion proteins. Twelve virion proteins were identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and mass spectrometry; all were present in both 80␣ and SaPI1 virions, and all were encoded by 80␣. No SaPI1-encoded proteins were detected. This confirms the prediction that SaPI1 is encapsidated in a virion assembled from helper phage-encoded proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 27 publications
0
73
0
Order By: Relevance
“…In particular, carboxy-terminal degradation was observed for StB27 and StB20 tail tape measure proteins (TMP) (Fig. 3B, band 1, and C, bands 1 and 2), as previously reported in staphylococcal phages (62). A structural function could be assigned to 32 proteins, including 11 proteins listed as hypothetical proteins in GenBank (see Tables S2, S3, and S4 in the supplemental material).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In particular, carboxy-terminal degradation was observed for StB27 and StB20 tail tape measure proteins (TMP) (Fig. 3B, band 1, and C, bands 1 and 2), as previously reported in staphylococcal phages (62). A structural function could be assigned to 32 proteins, including 11 proteins listed as hypothetical proteins in GenBank (see Tables S2, S3, and S4 in the supplemental material).…”
Section: Resultsmentioning
confidence: 61%
“…These proteins are related to the well-characterized and highly conserved tailassociated GP61 protein of the staphylococcal phage phiMR11. GP61 is thought to be involved in cell host lysis during phage adsorption (13,14,53,62). The GP61 homolog in StB12 is encoded by the three successive ORF64, ORF65, and ORF66 that are interrupted by two putative group I introns at positions 37063 to 37307 and 37542 to 37918.…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrate, using a mutational analysis, that the same proteins encoded by the distantly related phage 80␣ are used for SaPIbov1 and SaPI1 particle formation. This last result was anticipated by Tallent and coworkers, who analyzed by direct comparison of virion proteins the relationship between the compositions of SaPI1 transducing particles and those of helper phage 80␣ (16). However, in that previous study, no additional characterization of the proteins other than their identification was performed.…”
mentioning
confidence: 68%
“…Effects of phage 80␣ mutants on SaPI transfer. In a recent study with phage 80␣ and SaPI1, Tallent and coworkers identified 12 virion proteins from a sample containing SaPI1 particles (16). Since the most abundant proteins reported were homologous to those identified in this study and since no additional characterization of these proteins was performed in the previous study, we decided to obtain mutants with mutations in the 80␣ genes showing identity with the 11 genes characterized here.…”
Section: Vol 190 2008mentioning
confidence: 99%
“…Staphylococcus aureus is an important human pathogen, due largely to its ability to express a wide variety of virulence factors and antimicrobial resistance determinants which are often encoded by mobile genetic elements (7,10,21,24,25,39,56). Methicillin-resistant S. aureus (MRSA) infections are a major public health problem worldwide, both in hospitals and in the community, although the incidence varies.…”
mentioning
confidence: 99%